Polisi Syariah: Keamanan untuk Siapa? - Haryanto, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2014)
This paper is about community policing under Islamic Shariâa and its position in human security. This paper is intended to explain the characteristics and security paradigm in case Wilayatul Hisbah (Shariâa Police) in the province of Aceh. This paper connects the Shariâa police presence to human security, as well as how the characteristics of the security actors associated with maintaining order in the society of Aceh (community policing) are. As a result, the security paradigm in Aceh province is defined as the locality value, contradictory to those offered in the human security - to be adopted in a democratic transition regime as in Indonesia.